Facile entry into the 1H-pyrrolo[3, 4-b]indolizine-1, 3(2H)-dione scaffold via intramolecular Rh(II) carbene trapping. (23rd November 2021) - Chupakhin, Evgeny; Bakulina, Olga; Dar'in, Dmitry; Krasavin, Mikhail
Graphical abstract: Abstract: An unusual reactivity of Rh(II) carbenes generated from ( E )-3-(2-pyridylmethylene)-4-diazopyrrolidine-2, 5-diones was discovered which led to a novel type of fluorescent annelated indolizines (X-ray confirmed structure). The reaction was found to be insensitive to substitution pattern at pyrrolidine nitrogen atom and delivered a series of nine novel indolizines in 74–94% yields. Photophysical properties of obtained indolizines were investigated, which proved them to be blue or green luminophores with absolute quantum yields up to 13.8%. The latter strongly depended on substitution pattern at pyrrolidine nitrogen atom.